Psychometric Properties of the Thai Mental Health Literacy Scale in Sixth-Year Medical Students - Gobhathai Sittironnarit (2022)
Objective: To assess the psychometric properties of the Thai Mental Health Literacy Scale (TMHLS) in sixth-year medical students. Materials and Methods: By using the purposive sampling method, we enrolled 202 participants in this study. Descriptive statistics were used to analyze demographic data. The index of item-objective congruence (IOC) was used to verify content validity. Exploratory factor analysis (EFA) was performed to establish the construct validity of the TMHLS. The internal consistency was estimated by computing Cronbach’s coefficient alpha. Results: The TMHLS had good content validity (IOC=.85) and construct validity. The EFA resulted in five factors, which included 32 of the 35 items and accounted for 46.86% of the variance. The factors were the ability to recognize mental disorders; confidentiality of mental health practitioners; skills of mental health information seeking; beliefs about mental illnesses; and attitudes toward patients with mental illness. The reliability coefficient of the TMHLS total test was.851, and reliability coefficient in subdomains were range from.197 to.872. Individuals who had a mental health professional as an intimate contact and individuals who had a history of seeking help from mental health professional(s) in person showed significantly higher mental health literacy than those who did not. Conclusions: The TMHLS has good psychometric properties. Dynamic knowledge transfer and exchange with a close mental health professional should be applied to promote mental health literacy in medical students